Base material with coating and preparation method and hot bending forming processing method thereof
By forming a peelable protective layer and a surface protective layer on the glass surface, the problem of difficulty in removing the surface protective layer during the glass molding process is solved, and the high cleanliness of the glass surface and the convenient removal of the coating are achieved.
Patent Information
- Application Number
- CN202411557908.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the surface protective layer is difficult to remove during the glass forming process, resulting in difficulty in post-cleaning.
A substrate having a coating is used, which includes a peelable protective layer and a surface protective layer. The peelable protective layer consists of silicone modified polycarbonate, coupling agent and filler, and is removed by a hot alkaline cleaning solution.
It realizes convenient removal of the protective layer, ensures the cleanliness of the glass surface, and avoids the appearance of the coating.
Smart Images

Figure CN119504148A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of glass coatings, and in particular to a substrate with a coating, a preparation method thereof, and a hot bending forming processing method. Background Art
[0002] Coating is a feasible method for heat insulation of automotive glass. There are two implementation routes: one is to coat the flat glass with a toughenable coating and then temper it, and the other is to coat the tempered glass with a heat insulation coating.
[0003] In order to directly form heat-insulating glass after tempering, CN107189501A discloses a heat-insulating coating that can be tempered, a preparation method thereof, and the heat-insulating tempered glass obtained therefrom. The nano-functional material includes at least one of nano-antimony tin oxide, nano-indium tin oxide, and nano-cesium tungsten oxide, and the nano-functional material also includes at least one of nano-cerium oxide and nano-zinc oxide. Nano-antimony tin oxide, nano-indium tin oxide, and nano-cesium tungsten oxide have strong absorption and reflectivity to infrared light, while nano-cerium oxide and nano-zinc oxide have strong absorption and reflectivity to ultraviolet light. The combination of various nano-functional materials can play a good heat-insulating role. However, it only considers the realization of a single heat-insulating function, but does not consider the reliability of its comprehensive performance in the actual process.
[0004] The advantage of tempering first and then applying the coating is that the thermal insulation coating does not have to be subjected to high temperatures above 600°C, and there is no need to consider whether the film structure can withstand high temperatures and the impact of high temperatures on the performance and appearance of the film structure. However, during the molding process of automotive glass, due to the presence of pollutants in the production line equipment and environment, pollutants remain on the surface of the glass, resulting in coating appearance defects in the subsequent preparation of the coating on the glass surface, such as shrinkage holes, pinholes, pits, etc. After research, it was found that by adding a heat-resistant protective layer to the glass surface before the glass is molded, the surface can be effectively prevented from being contaminated during the glass molding process, thereby reducing the appearance defects of the coating caused by glass contamination. If a protective layer is simply set on the glass surface, although it can prevent the glass surface from being contaminated, the protective layer faces the problem of being difficult to remove later. Summary of the invention
[0005] Based on this, it is necessary to provide a substrate with a coating and a preparation method thereof, as well as a hot bending forming processing method, so as to solve the problem that the protective layer is difficult to remove later.
[0006] One of the objects of the present invention is to provide a substrate having a coating, the scheme is as follows:
[0007] A substrate with a coating, comprising a substrate, a peelable protective layer and a surface protective layer arranged on the substrate, wherein the peelable protective layer is arranged between the substrate and the surface protective layer; the raw materials of the peelable protective layer include the following components in parts by mass:
[0008] 40-55 parts of organosilicon-modified polycarbonate, 5-10 parts of the first coupling agent and 10-20 parts of the filler.
[0009] In one embodiment, the organosilicon-modified polycarbonate is a block copolymer formed by connecting an organosiloxane segment with a polycarbonate segment.
[0010] In one embodiment, the organosilicon-modified polycarbonate has a structure shown in formula (1);
[0011]
[0012] In formula (1), R1 is selected from C1-C5 alkyl, R2-R5 are independently selected from hydrogen atom, halogen atom, C1-C5 alkyl, C1-C5 alkoxy, aromatic group; m is in the range of 3-20, x is in the range of 50-1000, and y is in the range of 3-50.
[0013] In one embodiment, the first coupling agent includes a first titanate coupling agent.
[0014] In one embodiment, the first titanate coupling agent is selected from one or more of isopropyl titanate, tetrabutyl titanate, bis(dioctyl pyrophosphate)ethylene titanate, tetraisopropyl di(dioctyl phosphite) titanate and isopropyl tri(dioctyl pyrophosphate) titanate.
[0015] In one embodiment, the filler is selected from one or more of aluminum powder, calcium carbonate, pearl powder, mica, wollastonite, talc, kaolin and glass fiber.
[0016] In one embodiment, the raw material of the strippable protective layer further includes 30 parts to 50 parts of a first solvent by weight.
[0017] In one embodiment, the first solvent includes one or more of propylene glycol methyl ether acetate, dichloromethane, acetone, ethyl acetate and butyl acetate.
[0018] In one embodiment, the raw material of the strippable protective layer further includes 0.01 to 1 part of a first auxiliary agent by weight.
[0019] In one embodiment, the first auxiliary agent includes a first leveling agent.
[0020] In one embodiment, the first leveling agent is selected from one or more of polyether-modified siloxane, polyester-modified polymethyl alkyl siloxane and polyether polyester-modified hydroxyl-containing polysiloxane.
[0021] In one embodiment, the raw materials of the surface protection layer include the following components by mass:
[0022] 15-25 parts of silicon compound, 1-5 parts of titanium compound, 0.1-5 parts of filler, 5-15 parts of second coupling agent, 0.01-1 parts of catalyst, 1-10 parts of water;
[0023] In one embodiment, the silicon compound includes one or more of silicate and alkoxysilane, and the titanium compound includes one or more of titanate and titanium salt.
[0024] In one embodiment, the silicate is selected from one or more of methyl orthosilicate and ethyl orthosilicate.
[0025] In one embodiment, the alkoxysilane is selected from one or more of methyltrimethoxysilane, triethoxyhydrogensilane and dimethyldimethoxysilane.
[0026] In one embodiment, the titanate is selected from one or more of tetrabutyl titanate and tetraisopropyl titanate.
[0027] In one embodiment, the titanium salt is selected from one or more of titanium trichloride and titanium tetrachloride.
[0028] In one embodiment, the second coupling agent includes one or more of a silane coupling agent and a second titanate coupling agent;
[0029] In one embodiment, the silane coupling agent is selected from one or more of 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0030] In one embodiment, the second titanate coupling agent is selected from one or more of bis(dioctyl pyrophosphate)ethylene titanate, tetraisopropyl di(dioctyl phosphite) titanate and isopropyl tri(dioctyl pyrophosphate) titanate.
[0031] In one embodiment, the filler is selected from one or more of a silicon dioxide dispersion, a titanium dioxide dispersion and a zirconium oxide dispersion.
[0032] In one embodiment, the solid content of the silicon dioxide dispersion is 10%-30%.
[0033] In one embodiment, the solid content of the titanium dioxide dispersion is 10%-30%.
[0034] In one embodiment, the solid content of the zirconium oxide dispersion is 10%-30%.
[0035] In one embodiment, the raw material of the surface protection layer further includes 40 parts to 70 parts of a second solvent by weight.
[0036] In one embodiment, the second solvent is selected from one or more of methanol, ethanol, propanol, isopropanol, butanol and propylene glycol methyl ether.
[0037] In one embodiment, the catalyst is selected from one or more of acetic acid, hydrochloric acid, nitric acid, citric acid, oxalic acid and glycolic acid.
[0038] In one embodiment, the raw material of the surface protection layer further includes 0.1 to 2 parts of a second auxiliary agent by weight.
[0039] In one embodiment, the second auxiliary agent includes a second leveling agent.
[0040] In one embodiment, the second leveling agent is selected from one or more of polyether-modified siloxane, polyester-modified polymethyl alkyl siloxane and polyether polyester-modified hydroxyl-containing polysiloxane.
[0041] In one embodiment, the thickness of the peelable protective layer is 2 μm-6 μm, and the thickness of the surface protective layer is 1 μm-3 μm.
[0042] In one embodiment, the substrate comprises a glass member; or
[0043] The substrate comprises a glass member and a functional metal layer disposed on the glass member, and the strippable protective layer is in direct contact with the functional metal layer; or
[0044] The substrate comprises a glass member and a functional metal oxide layer disposed on the glass member, and the strippable protective layer is in direct contact with the functional metal oxide layer; or
[0045] The substrate comprises a glass member and an organic coating disposed on the glass member, and the strippable protective layer is in direct contact with the organic coating; or
[0046] The substrate comprises a glass member and an inorganic coating disposed on the glass member, and the strippable protective layer is in direct contact with the inorganic coating; or
[0047] The substrate includes a glass member and an organic-inorganic hybrid coating disposed on the glass member, and the strippable protective layer is in direct contact with the organic-inorganic hybrid coating.
[0048] Another object of the present invention is to provide a method for preparing a substrate having a coating as described in any of the above embodiments, the scheme is as follows:
[0049] A method for preparing a substrate with a coating comprises the following steps:
[0050] forming the strippable protective layer on a substrate;
[0051] The surface protection layer is formed on a side of the strippable protection layer away from the substrate.
[0052] In one embodiment, the step of forming the peelable protective layer comprises:
[0053] Mixing 40-55 parts of the organosilicon-modified polycarbonate, 5-10 parts of the first coupling agent, and 10-20 parts of the filler to prepare a first coating liquid;
[0054] The first coating liquid is applied on the surface of the substrate and dried to form the peelable protective layer.
[0055] The viscosity of the first coating liquid is 1 cP-100 cP.
[0056] In one embodiment, the step of forming the surface protection layer comprises:
[0057] Mix 15-25 parts of a silicon compound, 1-5 parts of a titanium compound, 0.1-5 parts of a filler, 5-15 parts of a second coupling agent, 0.01-1 parts of a catalyst, and 1-10 parts of water to prepare a second coating liquid;
[0058] The second coating liquid is applied on the peelable protective layer and cured to form the surface protective layer.
[0059] The viscosity of the second coating liquid is 1 cP-100 cP.
[0060] Another object of the present invention is to provide a substrate with a coating, the scheme is as follows:
[0061] A hot bending forming method comprises the following steps:
[0062] The substrate with the coating is prepared by the preparation method described in any one of the above embodiments, wherein the coating includes the strippable protective layer and the surface protective layer;
[0063] Performing hot bending forming on the substrate with the coating to obtain a formed body;
[0064] The molded body is cleaned with a cleaning liquid to remove the coating, wherein the cleaning liquid includes an alkaline substance.
[0065] In one embodiment, the pH value of the cleaning solution is 11-13.
[0066] In one of the embodiments, during the cleaning process, the temperature of the cleaning solution is 60°C-80°C.
[0067] In one embodiment, the cleaning solution further contains a surfactant.
[0068] In one embodiment, the surfactant is selected from one or more of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, isomeric alcohol polyoxyethylene ether, secondary alcohol polyoxyethylene ether, and alkyl polyoxyethylene polyoxypropylene.
[0069] In one embodiment, the cleaning process is assisted by ultrasonic treatment.
[0070] In one embodiment, the frequency of the ultrasonic treatment is 40kHz-80kHz, and the power is 10kW-20kW.
[0071] Compared with the conventional technology, the substrate with coating, the preparation method thereof, and the hot bending forming processing method have the following beneficial effects:
[0072] The above-mentioned substrate with coating and its preparation method form a strippable protective layer and a surface protective layer on the substrate, wherein the surface protective layer mainly acts on the surface of the substrate to prevent the substrate from being exposed to the external environment before the hot forming process, and to prevent the substrate from being contaminated and damaged by friction during the hot forming process. In parts by mass, the raw materials of the strippable protective layer include 40-55 parts of organosilicon-modified polycarbonate, 5-10 parts of the first coupling agent and 10-20 parts of filler, and the strippable protective layer is used to connect the substrate and the surface protective layer. In the strippable protective layer, the organosilicon-modified polycarbonate has good heat resistance. Since the heat resistance of the substrate with coating is the key to glass forming, the present invention assists the organosilicon-modified polycarbonate to further improve its heat resistance by adding fillers, so that the strippable protective layer has good heat resistance to meet the requirements of hot bending forming of the substrate with coating. By adding the first coupling agent, the coating is not easy to separate from the substrate during high temperature processing. In addition, the strippable protective layer can be removed by washing with a hot alkaline cleaning solution, making it easy to separate the coating from the substrate, and obtaining glass with excellent surface cleanliness after treatment.
[0073] The above-mentioned hot bending forming processing method can obtain corresponding beneficial effects by processing the substrate with coating prepared by the preparation method described in any of the above-mentioned embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 is a schematic structural diagram of a substrate with a coating according to an embodiment;
[0075] Figure 2 is a schematic flow chart of a method for preparing a substrate with a coating according to an embodiment;
[0076] Figure 3 A schematic flow chart of the steps for forming a surface protection layer;
[0077] Figure 4 The figure is a schematic flow chart of a hot bending forming method according to an embodiment.
[0078] Description of reference numerals:
[0079] 100. A substrate with a coating; 110. A substrate; 120. A peelable protective layer; 130. A surface protective layer. DETAILED DESCRIPTION
[0080] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0081] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0082] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0083] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0084] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0085] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0086] The term "alkyl" refers to a saturated hydrocarbon comprising a primary carbon atom, a secondary carbon atom, a tertiary carbon atom, a quaternary carbon atom, or a combination thereof. A phrase comprising the term, for example, "C1-C5 alkyl" refers to an alkyl comprising 1 to 5 carbon atoms, each occurrence of which may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl. The alkyl group may be straight chain or branched. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(CH3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3).
[0087] The term "alkoxy" refers to a group having an -O-alkyl group, i.e., an alkyl group as defined above is connected to a parent core structure via an oxygen atom. Phrases including this term, for example, "C1-C5 alkoxy" refers to an alkyl group comprising 1-5 carbon atoms, each occurrence of which may be independently C1 alkoxy, C2 alkoxy, C3 alkoxy, C4 alkoxy, C5 alkoxy. Alkoxy may be linear or branched. Suitable examples include, but are not limited to, methoxy (-O-CH3 or -OMe), ethoxy (-O-CH2CH3 or -OEt) and tert-butoxy (-OC(CH3)3 or -OtBu).
[0088] "Aromatic group" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom, which can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. Suitable examples include, but are not limited to, benzene, biphenyl, naphthalene, anthracene, phenanthrene and their derivatives.
[0089] "Halogen" or "halo" refers to F, Cl, Br or I.
[0090] The present invention provides a substrate having a coating.
[0091] like Figure 1 As shown, a substrate 100 with a coating in one embodiment includes a substrate 110, and a strippable protective layer 120 and a surface protective layer 130 disposed on the substrate 110, wherein the strippable protective layer 120 is disposed between the substrate 110 and the surface protective layer 130. In parts by mass, the strippable protective layer 120 includes 40 parts to 55 parts of organosilicon-modified polycarbonate, 5 parts to 10 parts of a first coupling agent, and 10 parts to 20 parts of a filler.
[0092] The above-mentioned substrate with coating and its preparation method form a strippable protective layer and a surface protective layer on the substrate, wherein the surface protective layer mainly acts on the surface of the substrate to prevent the substrate from being exposed to the external environment before the thermoforming process, and to prevent the substrate from being contaminated and damaged by friction during the thermoforming process. The strippable protective layer includes 40-55 parts of organosilicon-modified polycarbonate, 5-10 parts of a first coupling agent and 10-20 parts of a filler, which is used to connect the substrate and the surface protective layer. In the strippable protective layer, the organosilicon-modified polycarbonate has good heat resistance. The heat resistance of the strippable protective layer is the key to the glass forming process by adding fillers to assist the organosilicon-modified polycarbonate in improving its heat resistance. By adding the first coupling agent, the coating is not easy to separate from the substrate during high-temperature processing. In addition, the strippable protective layer can be removed by cleaning with a hot alkaline cleaning solution, so that the coating is easy to separate from the substrate, and glass with excellent surface cleanliness is obtained after treatment.
[0093] The thermal decomposition temperature of the organosilicon-modified polycarbonate is above 450°C, for example, the thermal decomposition temperature is 450°C-600°C. The present invention further enhances the heat resistance of the organosilicon-modified polycarbonate by adding fillers, so that the peelable protective layer can withstand high temperatures above 600°C, to ensure that the peelable protective layer will not be powdered and detached during the thermal bending process of the substrate 110. The thermal decomposition temperature can be obtained by thermal analysis test methods such as DSC (differential scanning calorimetry) and TG (thermogravimetric analysis).
[0094] In some examples, the strippable protective layer 120 is prepared from a first coating solution, and the first coating solution includes the following components in parts by weight:
[0095] 40-55 parts of organosilicon-modified polycarbonate, 5-10 parts of a first coupling agent and 10-20 parts of a filler.
[0096] The first coating liquid includes 40 parts to 55 parts of organosilicon-modified polycarbonate as the main film-forming substance. Compared with general polycarbonate, organosilicon-modified polycarbonate has better high temperature resistance. Furthermore, the mass fraction of organosilicon-modified polycarbonate in the first coating liquid is preferably 45 parts to 50 parts. In some of the examples, the mass fraction of organosilicon-modified polycarbonate contained in the first coating liquid is, for example, 40 parts, 42 parts, 45 parts, 47 parts, 50 parts, 52 parts, 55 parts, etc.
[0097] In some of the examples, the organosilicon-modified polycarbonate is a block copolymer formed by connecting an organosiloxane segment with a polycarbonate segment.
[0098] Furthermore, the organosilicon-modified polycarbonate has a structure represented by formula (1).
[0099]
[0100] In formula (1), R1 is selected from C1-C5 alkyl, R2-R5 are independently selected from hydrogen atom, halogen atom, C1-C5 alkyl, C1-C5 alkoxy, aromatic group. m is in the range of 3-20, x is in the range of 50-1000, and y is in the range of 3-50.
[0101] Furthermore, in some of the examples, in formula (1), R2-R5 are independently selected from a hydrogen atom, a C1-C5 alkyl group, and a C1-C5 alkoxy group.
[0102] Furthermore, in some of the examples, in formula (1), R1 is selected from C1-C3 alkyl, and R2-R5 are independently selected from hydrogen atom, C1-C3 alkyl, and C1-C3 alkoxy.
[0103] Furthermore, in some of the examples, in formula (1), R1 is selected from C1-C3 alkyl, and R2-R5 are independently selected from hydrogen atom, methyl, and methoxy.
[0104] In some of the examples, at least one of R2-R5 is a C1-C5 alkoxy group.
[0105] In some of these examples, the organosilicon-modified polycarbonate has a structure shown in formula (2).
[0106]
[0107] The first coating liquid includes 5-10 parts of the first coupling agent. Further, the first coating liquid includes 8-9 parts of the first coupling agent. In some examples, the mass fraction of the first coupling agent contained in the first coating liquid is, for example, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, etc.
[0108] In some examples, the first coupling agent includes a first titanate coupling agent.
[0109] In some examples, the first titanate coupling agent is selected from one or more of isopropyl titanate, tetra-n-butyl titanate, bis(dioctyl pyrophosphate)ethylene titanate, tetraisopropyl di(dioctyl phosphite) titanate and isopropyl tri(dioctyl pyrophosphate) titanate.
[0110] The first coating liquid includes 10-20 parts of filler, and the filler can help the silicone-modified polycarbonate improve its heat resistance. Further, the first coating liquid includes 16-18 parts of filler. In some examples, the mass fraction of the filler contained in the first coating liquid is, for example, 15 parts, 15.5 parts, 16 parts, 16.5 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts, 19.5 parts, 20 parts, etc.
[0111] Optionally, the filler is, for example but not limited to, one or more of aluminum powder, calcium carbonate, pearl powder, mica, wollastonite, talc, kaolin and glass fiber.
[0112] In some examples, the filler includes 2-4 parts of aluminum powder, 2-4 parts of talc powder, and 3-5 parts of pearl powder. Further, in some examples, the filler includes 3 parts of aluminum powder, 3 parts of talc powder, and 4 parts of pearl powder.
[0113] In some examples, the first coating solution further comprises 30 parts to 50 parts by weight of the first solvent. Further, the first solvent in the first coating solution preferably has a weight percentage of 35 parts to 40 parts.
[0114] In some of the examples, the mass fraction of the first solvent contained in the first coating liquid is, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, etc.
[0115] The first solvent is, for example, but not limited to, one or more of propylene glycol methyl ether acetate, dichloromethane, acetone, ethyl acetate, and butyl acetate.
[0116] In some of the examples, the first coating liquid further contains 0.01-1 part of the first auxiliary agent. Further, the first coating liquid contains 0.1-0.5 part of the first auxiliary agent. In some of the examples, the mass fraction of the first auxiliary agent contained in the first coating liquid is, for example, 0.01 part, 0.05 part, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.
[0117] In some examples, the first auxiliary agent includes a first leveling agent.
[0118] Optionally, the first leveling agent is, for example, but not limited to, one or more of polyether-modified siloxane, polyester-modified polymethyl alkyl siloxane, and polyether polyester-modified hydroxyl-containing polysiloxane. Among them, polyether-modified siloxane is, for example, one or more of BYK-327, BYK-330, BYK-342, BYK-346, and BYK-349. Polyester-modified polymethyl alkyl siloxane is, for example, one or more of BYK-310, BYK-314, BYK-320, BYK-322, and BYK-323. Polyether polyester-modified hydroxyl-containing polysiloxane is, for example, one or more of BYK-370, BYK-373, and BYK-375.
[0119] In some examples, the viscosity of the first coating liquid is 1 cP-100 cP. Further, the viscosity of the first coating liquid is preferably 5 cP-30 cP. In some examples, the viscosity of the first coating liquid is, for example, 5 cP, 10 cP, 20 cP, 30 cP, 40 cP, 50 cP, 60 cP, 70 cP, 80 cP, 90 cP, 100 cP, etc.
[0120] In some examples, the surface protection layer 130 is prepared from a second coating solution. The second coating solution includes the following components in parts by weight:
[0121] 15-25 parts of silicon compound, 1-5 parts of titanium compound, 0.1-5 parts of filler, 5-15 parts of second coupling agent, 0.01-1 parts of catalyst and 1-10 parts of water.
[0122] The silicon compound includes one or more of silicate and alkoxysilane, and the titanium compound includes one or more of titanate and titanium salt.
[0123] The second coating liquid can form a protective coating with high wear resistance after drying and curing, and the protective coating can still maintain a high visible light transmittance after a certain degree of wear.
[0124] The second coating liquid includes 15 to 25 parts of silicon compound. Further, the mass fraction of silicon compound in the second coating liquid is preferably 15 to 20 parts.
[0125] In some of the examples, the mass fraction of the silicon compound contained in the second coating liquid is, for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, etc.
[0126] In some examples, the silicate is, for example but not limited to, one or more of methyl orthosilicate and ethyl orthosilicate.
[0127] In some examples, the alkoxysilane is, for example but not limited to, one or more of methyltrimethoxysilane, triethoxyhydrogensilane, and dimethyldimethoxysilane.
[0128] The second coating liquid includes 1 to 5 parts of a titanium compound. Further, the mass fraction of the titanium compound in the second coating liquid is preferably 1.5 to 3 parts.
[0129] In some of the examples, the mass fraction of the titanium compound contained in the second coating solution is, for example, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.
[0130] In some examples, the titanate is, for example but not limited to, one or more of tetrabutyl titanate and tetraisopropyl titanate.
[0131] In some examples, the titanium salt is, for example but not limited to, one or more of titanium trichloride and titanium tetrachloride.
[0132] The second coating liquid includes 5 to 15 parts of the second coupling agent. Further, the weight fraction of the second coupling agent in the second coating liquid is preferably 10 to 12 parts.
[0133] In some of the examples, the mass fraction of the second coupling agent contained in the second coating liquid is, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.
[0134] In some examples, the second coupling agent includes one or more of a silane coupling agent and a titanate coupling agent.
[0135] In some of the examples, the silane coupling agent is, for example, but not limited to, one or more of 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0136] In some examples, the titanate coupling agent is, for example, but not limited to, one or more of bis(dioctylpyrophosphate)ethylene titanate, tetraisopropyldi(dioctylphosphite)titanate, and isopropyltri(dioctylpyrophosphate)titanate.
[0137] The second coating liquid includes 0.1 to 5 parts of filler. Further, the weight fraction of the filler in the second coating liquid is preferably 3.5 to 5 parts.
[0138] In some of the examples, the mass fraction of the filler contained in the second coating liquid is, for example, 0.2 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.
[0139] In some examples, the filler is, for example but not limited to, one or more of a silica dispersion, a titania dispersion, and a zirconium oxide dispersion.
[0140] The solid content of the silicon dioxide dispersion is 10%-30%, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, etc. The solid content of the titanium dioxide dispersion is 10%-30%, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, etc. The solid content of the zirconium oxide dispersion is 10%-30%, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, etc.
[0141] The second coating liquid includes 0.01 to 1 part of a catalyst. Further, the mass fraction of the catalyst in the second coating liquid is preferably 0.2 to 0.5 parts.
[0142] In some of the examples, the mass fraction of the catalyst contained in the second coating liquid is, for example, 0.02 parts, 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc.
[0143] In some examples, the catalyst is, for example but not limited to, one or more of acetic acid, hydrochloric acid, nitric acid, citric acid, oxalic acid, and glycolic acid.
[0144] The second coating liquid includes 1 to 10 parts of water. Further, the mass fraction of water in the second coating liquid is preferably 6 to 8 parts.
[0145] In some of the examples, the mass fraction of water contained in the second coating liquid is, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.
[0146] In some examples, the water is deionized water.
[0147] The second coating liquid further comprises 40-70 parts by weight of the second solvent. Further, the second coating liquid preferably comprises 50-60 parts by weight of the second solvent.
[0148] In some of the examples, the mass fraction of the second solvent contained in the second coating liquid is, for example, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, etc.
[0149] The second solvent is, for example, but not limited to, one or more of methanol, ethanol, propanol, isopropanol, butanol, and propylene glycol methyl ether.
[0150] In one example, the second coating liquid further includes 0.1 to 2 parts by weight of the second auxiliary agent. Furthermore, the second coating liquid preferably includes 0.5 to 1 part by weight of the second auxiliary agent.
[0151] In some of the examples, the second additive contained in the second coating liquid is, for example, 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, etc.
[0152] In some examples, the second auxiliary agent includes a second leveling agent.
[0153] In some examples, the second leveling agent is, for example, but not limited to, one or more of polyether-modified siloxane, polyester-modified polymethyl alkyl siloxane, and polyether polyester-modified hydroxyl-containing polysiloxane. Among them, polyether-modified siloxane is, for example, one or more of BYK-327, BYK-330, BYK-342, BYK-346, and BYK-349. Polyester-modified polymethyl alkyl siloxane is, for example, one or more of BYK-310, BYK-314, BYK-320, BYK-322, and BYK-323. Polyether polyester-modified hydroxyl-containing polysiloxane is, for example, one or more of BYK-370, BYK-373, and BYK-375.
[0154] In some examples, the viscosity of the second coating liquid is 1 cP-100 cP. Further, the viscosity of the second coating liquid is preferably 5 cP-30 cP. In some examples, the viscosity of the second coating liquid is, for example, 5 cP, 10 cP, 20 cP, 30 cP, 40 cP, 50 cP, 60 cP, 70 cP, 80 cP, 90 cP, 100 cP, etc.
[0155] In some examples, the total thickness of the coating is 3 μm-9 μm. Further, the total thickness of the coating is preferably 4 μm-9 μm. In some examples, the total thickness of the coating is, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, etc.
[0156] In some examples, the thickness of the peelable protective layer 120 is 2 μm-6 μm. Further, the thickness of the peelable protective layer 120 is preferably 3 μm-6 μm. In some examples, the thickness of the peelable protective layer 120 is, for example, 2 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, etc.
[0157] In some examples, the thickness of the surface protection layer 130 is 1 μm-3 μm. Further, the thickness of the surface protection layer 130 is preferably 1 μm-2 μm. In some examples, the thickness of the surface protection layer 130 is, for example, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, etc.
[0158] In some examples, substrate 110 includes a glass member.
[0159] In some examples, the substrate 110 further includes a functional metal layer disposed on the glass member, and the strippable protective layer 120 is in direct contact with the functional metal layer.
[0160] In some examples, the substrate 110 further includes a functional metal oxide layer disposed on the glass member, and the strippable protective layer 120 is in direct contact with the functional metal oxide layer.
[0161] In some examples, the substrate 110 further includes an organic coating disposed on the glass member, and the strippable protective layer 120 is in direct contact with the organic coating.
[0162] In some examples, the substrate 110 further includes an inorganic coating layer disposed on the glass member, and the strippable protective layer 120 is in direct contact with the inorganic coating layer.
[0163] In some of the examples, the substrate 110 further includes an organic-inorganic hybrid coating disposed on the glass member, and the strippable protective layer 120 is in direct contact with the organic-inorganic hybrid coating.
[0164] It should be noted that the surface of the substrate 110 may be a flat surface or a curved surface.
[0165] It should be noted that the glass in the present invention can be automobile glass, such as door window glass, car triangular window glass, car rear windshield, etc. Automobile glass needs to be subjected to high temperature heat treatment and molding, and the coating of the present invention can be subjected to high temperature heat treatment and molding along with the glass without cracks.
[0166] After high-temperature bending, the coating on the bent glass is peeled off. The change value of the glass water contact angle after the coating is peeled off is less than or equal to 1°. The change value of the surface energy of the glass after the coating is peeled off is less than 2mN / m.
[0167] The substrate 100 with coating comprises a peelable protective layer 120 and a surface protective layer 130 formed on the substrate 110, wherein the surface protective layer 130 mainly acts on the surface of the substrate to prevent the substrate from being exposed to the external environment before the thermoforming process, and to prevent the substrate from being contaminated and damaged by friction during the thermoforming process. The peelable protective layer 120 comprises organosilicon-modified polycarbonate, which is used to connect the substrate 110 and the surface protective layer 130. The organosilicon-modified polycarbonate can be removed by washing with a hot alkaline cleaning solution, so that the coating is easy to be separated from the substrate 110.
[0168] Furthermore, the present invention also provides a method for preparing a substrate 100 having a coating, comprising the following steps:
[0169] forming a peelable protective layer on a substrate;
[0170] A surface protection layer is formed on a side of the strippable protection layer away from the substrate.
[0171] like Figure 2 As shown, a method for preparing a substrate 100 with a coating according to an embodiment includes the following steps:
[0172] Step S110 , mixing 40 parts to 55 parts of organosilicon-modified polycarbonate, 5 parts to 10 parts of a first coupling agent, and 10 parts to 20 parts of a filler to prepare a first coating liquid.
[0173] In step S120 , a first coating liquid is applied to the surface of the substrate 110 , and dried to form a peelable protective layer 120 .
[0174] Step S130 , forming a surface protection layer 130 on the peelable protection layer 120 .
[0175] In some examples, before applying the first coating solution to the surface of the substrate 110 (step S120), the surface of the substrate 110 is pretreated so that the water contact angle of the surface of the substrate 110 is less than 10°. For example, by pretreating the surface of the substrate 110, the water contact angle of the surface of the substrate 110 is 1°-9°, specifically 1°, 2°, 3°, 4°, 5°, 6°, 7°, 8°, 9°, etc.
[0176] In some examples, in step S120, the temperature at which the first coating liquid is dried is 60° C.-100° C. Further, in some examples, the temperature at which the first coating liquid is dried is 70° C.-90° C. In some examples, the temperature at which the first coating liquid is dried is, for example, 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C., etc.
[0177] In some of the examples, in step S120, the first coating liquid is dried for 5 min to 60 min. Further, in some of the examples, the first coating liquid is dried for 20 min to 50 min. In some of the examples, the first coating liquid is dried for 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0178] Optionally, in step S120 , the method of coating the first coating liquid on the substrate 110 may be, but is not limited to, spray coating, scraper coating, spin coating, roller coating, etc.
[0179] Preferably, in step S120, the cleanliness of the environment is controlled to be above Class 10,000.
[0180] Preferably, in step S120, the temperature of the environment ranges from 10°C to 25°C.
[0181] Preferably, in step S120, the humidity of the environment is greater than or equal to 50% RH and less than or equal to 80% RH.
[0182] After step S120 , the substrate 110 with the strippable protective layer 120 is subjected to a temperature reduction treatment, for example, to a temperature of 10° C.-25° C.
[0183] like Figure 3 As shown, in some examples, the step of forming the surface protection layer 130 (step S130) includes:
[0184] Step S131, 15-25 parts of silicon compound, 1-5 parts of titanium compound, 0.1-5 parts of filler, 5-15 parts of second coupling agent, 0.01-1 parts of catalyst, and 1-10 parts of water are mixed to prepare a second coating liquid.
[0185] Step S132 , coating the second coating liquid on the peelable protective layer 120 , and curing the second coating liquid to form the surface protective layer 130 .
[0186] In step S131, the catalyst and water are premixed and stirred to obtain an aqueous solution containing the catalyst. The addition rate of the aqueous solution containing the catalyst is, for example, 4 g / min-1000 g / min. The stirring speed is, for example, 100 rpm-1000 rpm.
[0187] Preferably, in step S132, the cleanliness of the environment is controlled to be above Class 10,000.
[0188] Preferably, in step S132, the temperature of the environment ranges from 10°C to 25°C.
[0189] Preferably, in step S132, the humidity of the environment is greater than or equal to 50% RH and less than or equal to 80% RH.
[0190] In some of the examples, in step S132, the second coating liquid is cured at a temperature of 150° C.-190° C. Further, in some of the examples, the second coating liquid is cured at a temperature of 170° C.-190° C. In some of the examples, the second coating liquid is cured at a temperature of, for example, 150° C., 155° C., 160° C., 165° C., 170° C., 175° C., 180° C., 185° C., 190° C., etc.
[0191] In some of the examples, in step S132, the second coating liquid is cured for 30 min to 120 min. Further, in some of the examples, the second coating liquid is cured for 60 min to 90 min. In some of the examples, the second coating liquid is cured for 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc.
[0192] After step S132 , the substrate 110 with the surface protection layer 130 is subjected to a temperature reduction treatment, for example, to a temperature of 10° C.-25° C.
[0193] Furthermore, the present invention also provides a hot bending forming method.
[0194] like Figure 4 As shown, a hot bending forming method of an embodiment includes the following steps:
[0195] Step S210 , preparing the substrate 100 with a coating by the above-mentioned method for preparing the substrate with a coating.
[0196] Step S220 , performing hot bending forming processing on the substrate 100 with the coating to obtain a formed body.
[0197] Step S230: cleaning the formed body with a cleaning liquid to remove the coating. The cleaning liquid includes an alkaline substance.
[0198] In some of the examples, the pH value of the cleaning solution is 11 to 13. Further, in some of the examples, the pH value of the cleaning agent is 12 to 13. In some of the examples, the pH value of the alkaline solution is, for example, 11, 11.2, 11.4, 11.6, 11.8, 12, 12.2, 12.4, 12.6, 12.8, 13, etc.
[0199] Furthermore, the cleaning solution also includes a surfactant, which can better clean and remove the coating. In some examples, the surfactant includes a non-ionic surfactant.
[0200] Optionally, the surfactant is one or more of, for example but not limited to, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, isomeric alcohol polyoxyethylene ether, secondary alcohol polyoxyethylene ether, and alkyl polyoxyethylene polyoxypropylene.
[0201] In some of the examples, during the cleaning process, the temperature of the cleaning liquid is 60° C.-80° C. Further, in some of the examples, the temperature of the cleaning liquid is 60° C.-70° C. In some of the examples, the temperature of the cleaning liquid is, for example, 60° C., 62° C., 64° C., 66° C., 68° C., 70° C., 72° C., 74° C., 76° C., 78° C., 80° C., etc.
[0202] During the cleaning process, ultrasonic treatment is used to completely separate the coating from the substrate 110 .
[0203] In some of the examples, the frequency of the ultrasonic treatment is 40kHz-80kHz. The power of the ultrasonic treatment is 10kW-20kW. Further, in some of the examples, the frequency of the ultrasonic treatment is 60kHz-80kHz. The power of the ultrasonic treatment is 15kW-20kW.
[0204] In some examples, after step S230, the hot bending forming method further includes the following steps:
[0205] In step S240 , the substrate 110 is cleaned and dried.
[0206] The washing treatment is preferably performed with deionized water, the conductivity of which is, for example, 3 μS / cm-8 μS / cm, specifically, 3 μS / cm, 4 μS / cm, 5 μS / cm, 6 μS / cm, 7 μS / cm, 8 μS / cm, etc.
[0207] The drying temperature is, for example, 60°C-80°C, specifically 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, etc. The drying time is, for example, 1h-4h, specifically 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, etc.
[0208] The following specific examples are provided to further illustrate the present invention, but the present invention is not limited to the following specific implementation methods. The present invention provides the following specific examples for a better understanding of the present invention, and does not limit the protection scope of the present invention.
[0209] Example 1
[0210] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer, and wherein the filler used in the peelable protective layer is a composite filler.
[0211] Step 1: 45 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 18 parts of aluminum powder, 6 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and 0.2 parts of polyether-modified siloxane are mixed evenly. The mixture is stirred at 300 rpm for 4 hours at room temperature to obtain a first coating solution, which is then allowed to stand for 24 hours for standby use.
[0212]
[0213] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0214] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0215] Step 4: spray the second coating liquid onto the peelable protective layer. After leveling, cure at 180° C. for 60 min to obtain sample 1.
[0216] Sample 1 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of Sample 1 was observed and recorded.
[0217] Example 2
[0218] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0219] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0220] Step 1: Evenly mix 40 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 18 parts of pearl powder, 5 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and 0.2 parts of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0221] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0222] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0223] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain sample 2.
[0224] Sample 2 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of Sample 2 was observed and recorded.
[0225] Example 3
[0226] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0227] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0228] Step 1: 45 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 50 parts of ethyl acetate, 18 parts of talc, 10 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and 0.2 parts of polyether-modified siloxane are mixed evenly. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, which is then allowed to stand for 24 hours for standby use.
[0229] Step 2: Evenly mix 15 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 40 parts of propylene glycol methyl ether, 5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 1 part of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0230] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0231] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain sample 3.
[0232] Sample 3 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of Sample 3 was observed and recorded.
[0233] Example 4
[0234] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0235] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0236] Step 1: 55 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 20 parts of pearl powder, 6 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane are mixed evenly. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, which is then allowed to stand for 24 hours for standby use.
[0237] Step 2: Evenly mix 25 parts of tetraethyl orthosilicate, 1 part of tetrabutyl titanate, 70 parts of propylene glycol methyl ether, 0.1 part of zirconium oxide dispersion, 15 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 part of concentrated nitric acid, 10 parts of deionized water and 0.4 part of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0238] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0239] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain sample 4.
[0240] Sample 4 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of sample 4 was observed and recorded.
[0241] Example 5
[0242] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0243] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0244] Step 1: 45 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 3 parts of aluminum powder, 3 parts of pearl powder, 4 parts of talc, 6 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane are mixed evenly. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0245] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0246] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0247] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain sample 5.
[0248] Sample 5 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of Sample 5 was observed and recorded.
[0249] Example 6
[0250] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0251] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0252] Step 1: Evenly mix 50 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 12 parts of talc, 6 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0253] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0254] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0255] Step 4: spray the second coating liquid onto the peelable protective layer. After leveling, cure at 180° C. for 60 min to obtain sample 6.
[0256] Sample 6 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of Sample 6 was observed and recorded.
[0257] Example 7
[0258] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0259] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0260] Step 1: Evenly mix 50 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 15 parts of pearl powder, 8 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0261] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0262] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0263] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain sample 7.
[0264] Sample 7 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of Sample 7 was observed and recorded.
[0265] Example 8
[0266] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0267] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0268] Step 1: Evenly mix 50 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 18 parts of aluminum powder, 8 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0269] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0270] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0271] Step 4: spray the second coating liquid onto the peelable protective layer. After leveling, cure at 180° C. for 60 min to obtain sample 8.
[0272] Sample 8 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of Sample 8 was observed and recorded.
[0273] Example 9
[0274] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0275] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0276] Step 1: Evenly mix 50 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 4 parts of aluminum powder, 4 parts of pearl powder, 3 parts of talc, 8 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0277] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0278] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0279] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain sample 9.
[0280] Sample 9 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of sample 9 was observed and recorded.
[0281] Example 10
[0282] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0283] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0284] Step 1: Evenly mix 45 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 3 parts of aluminum powder, 3 parts of pearl powder, 4 parts of talc, 8 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0285] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0286] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0287] Step 4: spray the second coating liquid onto the peelable protective layer. After leveling, cure at 180° C. for 60 min to obtain sample 10.
[0288] The sample 10 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of the glass. After the sample 10 was naturally cooled to room temperature, the state of the sample 10 was observed and recorded.
[0289] Comparative Example 1
[0290] This comparative example is a glass with a coating, and the coating only includes a peelable protective layer.
[0291] The method for preparing the glass with coating of this comparative example comprises the following steps:
[0292] Step 1: 40 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 15 parts of pearl powder, 6 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and 0.2 parts of polyether-modified siloxane are mixed evenly. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, which is then allowed to stand for 24 hours for use.
[0293] Step 2: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer. Curing at 180° C. for 60 minutes to obtain comparative sample 1.
[0294] The comparative sample 1 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 minutes to simulate the high-temperature bending process of the glass. After naturally cooling to room temperature, the state of the comparative sample 1 was observed and recorded.
[0295] Comparative Example 2
[0296] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0297] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0298] Step 1: 30 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 18 parts of aluminum powder, 6 parts of tetraisopropyl di(dioctylphosphite) titanate and 0.2 parts of polyether-modified siloxane are mixed evenly. The mixture is stirred at 300 rpm for 4 hours at room temperature to obtain a first coating solution, which is then allowed to stand for 24 hours for standby use.
[0299] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0300] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0301] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 minutes to obtain comparative sample 2.
[0302] The comparative sample 2 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of the sample 2 was observed and recorded.
[0303] Comparative Example 3
[0304] This embodiment provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0305] The method for preparing the glass with coating of this embodiment comprises the following steps:
[0306] Step 1: 60 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 18 parts of aluminum powder, 6 parts of tetraisopropyl di(dioctylphosphite) titanate and 0.2 parts of polyether-modified siloxane are mixed evenly. The mixture is stirred at 300 rpm for 4 hours at room temperature to obtain a first coating solution, which is then allowed to stand for 24 hours for standby use.
[0307] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0308] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0309] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain comparative sample 3.
[0310] The comparative sample 3 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of the sample 3 was observed and recorded.
[0311] Comparative Example 4
[0312] This comparative example is a glass with a coating, which is only a surface protective layer.
[0313] The method for preparing the glass with coating of this comparative example comprises the following steps:
[0314] Step 1: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0315] Step 2: spray the second coating liquid on the glass surface, and after leveling, cure at 180° C. for 60 minutes to obtain comparative sample 4.
[0316] The comparative sample 4 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 minutes to simulate the high-temperature bending process of the glass. After naturally cooling to room temperature, the state of the comparative sample 2 was observed and recorded.
[0317] Comparative Example 5
[0318] This comparative example provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0319] The method for preparing the glass with coating of this comparative example comprises the following steps:
[0320] Step 1: Evenly mix 45 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 3 parts of aluminum powder, 3 parts of pearl powder, 4 parts of talc powder and 1 part of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for standby use.
[0321] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0322] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0323] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain comparative sample 5.
[0324] The comparative sample 5 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of the sample 5 was observed and recorded.
[0325] Comparative Example 6
[0326] This comparative example provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0327] The method for preparing the glass with coating of this comparative example comprises the following steps:
[0328] Step 1: Evenly mix 45 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 3 parts of aluminum powder, 3 parts of pearl powder, 4 parts of talc, 15 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0329] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0330] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0331] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain comparative sample 6.
[0332] The comparative sample 6 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 minutes to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of the sample 6 was observed and recorded.
[0333] Comparative Example 7
[0334] This comparative example provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0335] The method for preparing the glass with coating of this comparative example comprises the following steps:
[0336] Step 1: Evenly mix 50 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 24 parts of aluminum powder, 8 parts of tetraisopropyl di(dioctylphosphite) titanate and 1 part of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0337] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0338] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0339] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain comparative sample 7.
[0340] The comparative sample 7 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 min to simulate the high-temperature bending process of glass. After naturally cooling to room temperature, the state of the sample 7 was observed and recorded.
[0341] Comparative Example 8
[0342] This comparative example provides a glass with a coating, wherein the coating comprises a peelable protective layer and a surface protective layer, wherein the peelable protective layer is arranged between the glass and the surface protective layer.
[0343] Step 1: Evenly mix 50 parts of organosilicon-modified polycarbonate (structure as shown in formula (2)), 30 parts of ethyl acetate, 5 parts of aluminum powder, 8 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and 0.2 parts of polyether-modified siloxane. Stir at room temperature at a speed of 300 rpm for 4 hours to obtain a first coating solution, and let it stand for 24 hours for use.
[0344] Step 2: Evenly mix 20 parts of tetraethyl orthosilicate, 5 parts of tetrabutyl titanate, 60 parts of propylene glycol methyl ether, 3.5 parts of zirconium oxide dispersion, 5 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of concentrated nitric acid, 7 parts of deionized water and 0.4 parts of polyether modified siloxane. Stir at room temperature at a speed of 300 rpm for 8 hours to obtain a second coating solution, and let it stand for 24 hours for use.
[0345] Step 3: spray the first coating liquid onto the surface of the glass. After leveling, use a medium-wave infrared lamp to dry at 80° C. for 20 minutes and then cool to form a peelable protective layer.
[0346] Step 4: spray the second coating liquid onto the peelable protective layer, and after leveling, cure at 180° C. for 60 min to obtain comparative sample 8.
[0347] The comparative sample 8 was cooled to room temperature, transferred to a muffle furnace, and heated at 650°C for 10 minutes to simulate the high-temperature bending process of the glass. After naturally cooling to room temperature, the state of the comparative sample 8 was observed and recorded.
[0348] The following tests were performed on the coated glasses prepared in Examples 1-10 and Comparative Examples 1-8.
[0349] 1. Coating hardness test
[0350] After the spraying process is completed, the glass is usually wrapped with lining paper between two pieces of glass during transportation and storage to protect the glass and the coating. It is necessary to point out that the hardness value of the lining paper is 3H. In order to prevent the coating from being damaged during transportation, the hardness of the coating needs to be higher than 3H.
[0351] The test of coating hardness refers to GB / T6739-2006 standard. The test uses the MK-3018 electric pencil hardness tester produced by Shanghai Gaozhi Precision Instrument Co., Ltd. First, place the machine level on the test machine platform. Fix the substrate with the coating facing up on the experimental platform, and select the experimental pencils from the Zhonghua brand high-grade drawing pencils. There are 13 types, including 6B, 5B, 4B, 3B, 2B, B, HB, H, 2H, 3H, 4H, 5H, and 6H, among which 6H is the hardest and 6B is the softest. The protruding part of the pencil core is about 3-5mm. Insert the pencil into the 45° socket so that the pencil contacts the sample coating layer. Apply appropriate load to move the experimental platform uniformly at about 1cm / s in front of the experimenter to move the surface of the coating layer. The softest pencil grade that does not cause damage to the coating layer when it contacts the pencil core is considered as the hardness of the coating layer. The pencil tip needs to be re-grinded after each scrape, and the same grade pencil is repeated 5 times.
[0352] 2. Coating powdering level test
[0353] The substrate with coating is molded by BT machine to obtain a molded body, and an area with a size of 200mm*200mm is selected on the glass surface, and the coating powdering level is distinguished according to the number of coating powdering areas. The coating powdering level standard is shown in Table 1.
[0354] 3. Coating cleaning level test
[0355] The substrate with the coating is cleaned with a cleaning liquid. The temperature of the cleaning liquid is 60°C. The cleaning liquid includes sodium hydroxide and non-ionic surfactant alkylphenol polyoxyethylene ether, and the pH is 13. Ultrasonic treatment is used during the cleaning process. The frequency of the ultrasonic treatment is 100kHz and the power is 20kW.
[0356] An area of 200mm*200mm is selected on the glass surface, and the coating cleaning level is distinguished according to the number of areas where the coating has completely fallen off. The coating cleaning level standard is shown in Table 2.
[0357] The test results are shown in Table 3.
[0358] Table 1 Coating powdering grade
[0359] grade standard 0 Coating intact 1 The number of powdered areas is no more than 5 2 The number of powdered areas is greater than 5 and less than 10. 3 The number of powdered areas is greater than 10 and less than 15. 4 The number of powdered areas is greater than 15 and less than 20. 5 All coatings are powdered
[0360] Table 2 Coating cleaning grade standards
[0361] grade standard 0 All coatings have fallen off 1 The number of shedding areas is greater than 15 and less than 20 2 The number of shedding areas is greater than 10 and less than 15 3 The number of shedding areas is greater than 5 and less than 10 4 The shedding area is no more than 5
[0362] Table 3 Test results of Examples 1-10 and Comparative Examples 1-8
[0363]
[0364] Compared with Example 2, Comparative Example 1 only has a peelable protective layer, but no surface protective layer. The coating powdering levels of Example 1 and Comparative Example 1 both reach level 0, indicating that the peelable layer has good thermal stability. However, the coating hardness of Comparative Example 1 is relatively low, and there is a risk of coating damage during transportation on the production line. Compared with Example 1, Comparative Example 4 only has a surface protective layer, but no peelable protective layer. The coating powdering levels of Example 1 and Comparative Example 4 both reach level 0, and the hardness both reach 6H, indicating that the thermal stability and hardness of the surface protective layer are good. However, the subsequent cleaning effect of the coating of Comparative Example 2 is poor, and it is difficult to remove from the substrate.
[0365] Compared with Example 1, the amount of organosilicon-modified polycarbonate in the peelable protective layer of Comparative Example 2 is reduced, and the coating is naturally detached after curing, which does not meet the expected effect. Further comparison with Comparative Example 3 shows that the more the amount of organosilicon-modified polycarbonate added, the better. Too much addition of organosilicon-modified polycarbonate is not conducive to the formation of the peelable protective layer.
[0366] Compared with Example 7, the amount of filler added in the peelable protective layer of Comparative Example 8 is reduced, and the powdering level of the coating decreases, indicating that the addition of fillers is beneficial to improving the heat resistance of the high-temperature resistant coating. Compared with Example 8, the amount of filler added in Comparative Example 7 is higher, and cracking occurs in the coating after curing, which shows that the more filler added, the better.
[0367] Compared with Example 5, in Comparative Example 5, the first coupling agent was not added, and the strippable protective layer could not form a film, indicating that the addition of the first coupling agent improved the adhesion of the coating to the substrate to a certain extent. Further comparison with Comparative Example 6 shows that the more the first coupling agent is added, the better. Too much first coupling agent is added, which is not conducive to the strippable protective layer being stripped from the surface of the substrate.
[0368] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0369] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A substrate having a coating, characterized in that: It comprises a substrate, a peelable protective layer and a surface protective layer arranged on the substrate, wherein the peelable protective layer is arranged between the substrate and the surface protective layer; the raw materials of the peelable protective layer include the following components by weight: 40-55 parts of organosilicon-modified polycarbonate, 5-10 parts of the first coupling agent and 10-20 parts of the filler.
2. The substrate with a coating according to claim 1, characterized in that The organosilicon-modified polycarbonate is a block copolymer formed by connecting an organosiloxane segment with a polycarbonate segment.
3. The substrate with a coating according to claim 1, characterized in that The organosilicon-modified polycarbonate has a structure shown in formula (1); In formula (1), R1 is selected from C1-C5 alkyl, R2-R5 are independently selected from hydrogen atom, halogen atom, C1-C5 alkyl, C1-C5 alkoxy, aromatic group; m is in the range of 3-20, x is in the range of 50-1000, and y is in the range of 3-50.
4. The substrate with a coating according to claim 1, characterized in that The first coupling agent includes a first titanate coupling agent; Optionally, the first titanate coupling agent is selected from one or more of isopropyl titanate, tetra-n-butyl titanate, bis(dioctyl pyrophosphate)ethylene titanate, tetraisopropyl di(dioctyl phosphite) titanate and isopropyl tri(dioctyl pyrophosphate) titanate.
5. The substrate with a coating according to any one of claims 1 to 4, characterized in that The filler is selected from one or more of aluminum powder, calcium carbonate, pearl powder, mica, wollastonite, talc, kaolin and glass fiber.
6. The substrate with a coating according to any one of claims 1 to 4, characterized in that The raw material of the strippable protective layer further includes 30 parts to 50 parts of a first solvent by weight; Optionally, the first solvent includes one or more of propylene glycol methyl ether acetate, dichloromethane, acetone, ethyl acetate and butyl acetate.
7. The substrate with a coating according to any one of claims 1 to 4, characterized in that The raw material of the strippable protective layer further includes 0.01 to 1 part of a first auxiliary agent by weight; Optionally, the first auxiliary agent includes a first leveling agent; Optionally, the first leveling agent is selected from one or more of polyether-modified siloxane, polyester-modified polymethyl alkyl siloxane and polyether polyester-modified hydroxyl-containing polysiloxane.
8. The substrate with a coating according to any one of claims 1 to 4, characterized in that The raw materials of the surface protection layer include the following components by mass: 15-25 parts of silicon compound, 1-5 parts of titanium compound, 0.1-5 parts of filler, 5-15 parts of second coupling agent, 0.01-1 part of catalyst, and 1-10 parts of water.
9. The substrate with a coating according to claim 8, characterized in that The silicon compound includes one or more of silicate and alkoxysilane, and the titanium compound includes one or more of titanate and titanium salt.
10. The substrate with a coating according to claim 9, characterized in that The silicate is selected from one or more of methyl orthosilicate and ethyl orthosilicate; and / or The alkoxysilane is selected from one or more of methyltrimethoxysilane, triethoxyhydrogensilane and dimethyldimethoxysilane; and / or The titanate is selected from one or more of tetrabutyl titanate and tetraisopropyl titanate; and / or The titanium salt is selected from one or more of titanium trichloride and titanium tetrachloride.
11. The substrate with a coating according to claim 8, characterized in that The second coupling agent includes one or more of a silane coupling agent and a second titanate coupling agent; Optionally, the silane coupling agent is selected from one or more of 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; Optionally, the second titanate coupling agent is selected from one or more of bis(dioctyl pyrophosphate)ethylene titanate, tetraisopropyl di(dioctyl phosphite) titanate and isopropyl tri(dioctyl pyrophosphate) titanate.
12. The substrate with a coating according to claim 8, characterized in that The filler is selected from one or more of a silicon dioxide dispersion, a titanium dioxide dispersion and a zirconium oxide dispersion; Optionally, the solid content of the silicon dioxide dispersion is 10%-30%; Optionally, the solid content of the titanium dioxide dispersion is 10%-30%; Optionally, the solid content of the zirconium oxide dispersion is 10%-30%.
13. The substrate with a coating according to claim 8, characterized in that The raw material of the surface protection layer further includes 40 parts to 70 parts of a second solvent by mass; Optionally, the second solvent is selected from one or more of methanol, ethanol, propanol, isopropanol, butanol and propylene glycol methyl ether.
14. The substrate having a coating according to claim 8, characterized in that The catalyst is selected from one or more of acetic acid, hydrochloric acid, nitric acid, citric acid, oxalic acid and glycolic acid.
15. The substrate having a coating according to claim 8, characterized in that The raw materials of the surface protection layer further include 0.1 to 2 parts of a second auxiliary agent by weight; Optionally, the second auxiliary agent includes a second leveling agent; Optionally, the second leveling agent is selected from one or more of polyether-modified siloxane, polyester-modified polymethylalkylsiloxane and polyether-polyester-modified hydroxyl-containing polysiloxane.
16. The substrate with a coating according to any one of claims 1 to 4 and 9 to 15, characterized in that: The thickness of the strippable protective layer is 2 μm-6 μm, and the thickness of the surface protective layer is 1 μm-3 μm.
17. The substrate with a coating according to any one of claims 1 to 4 and 9 to 15, characterized in that: The substrate comprises a glass member; or The substrate comprises a glass member and a functional metal layer disposed on the glass member, and the strippable protective layer is in direct contact with the functional metal layer; or The substrate comprises a glass member and a functional metal oxide layer disposed on the glass member, and the strippable protective layer is in direct contact with the functional metal oxide layer; or The substrate comprises a glass member and an organic coating disposed on the glass member, and the strippable protective layer is in direct contact with the organic coating; or The substrate comprises a glass member and an inorganic coating disposed on the glass member, and the strippable protective layer is in direct contact with the inorganic coating; or The substrate includes a glass member and an organic-inorganic hybrid coating disposed on the glass member, and the strippable protective layer is in direct contact with the organic-inorganic hybrid coating.
18. A method for preparing a substrate having a coating according to any one of claims 1 to 17, characterized in that: The following steps are involved: forming the strippable protective layer on a substrate; The surface protection layer is formed on a side of the strippable protection layer away from the substrate.
19. The preparation method according to claim 18, characterized in that: The step of forming the peelable protective layer comprises: Mixing 40-55 parts of the organosilicon-modified polycarbonate, 5-10 parts of the first coupling agent, and 10-20 parts of the filler by mass to prepare a first coating liquid; The first coating liquid is applied on the surface of the substrate and dried to form the peelable protective layer.
20. The preparation method according to claim 19, characterized in that: The viscosity of the first coating liquid is 1 cP-100 cP.
21. The preparation method according to claim 18, characterized in that: The step of forming the surface protection layer comprises: By weight, 15-25 parts of a silicon compound, 1-5 parts of a titanium compound, 0.1-5 parts of a filler, 5-15 parts of a second coupling agent, 0.01-1 parts of a catalyst, and 1-10 parts of water are mixed to prepare a second coating solution; The second coating liquid is applied on the peelable protective layer and cured to form the surface protective layer.
22. The preparation method according to claim 21, characterized in that: The viscosity of the second coating liquid is 1 cP-100 cP.
23. A hot bending forming method, characterized in that: The following steps are involved: The substrate with the coating is prepared by the preparation method according to any one of claims 18 to 22, wherein the coating comprises the strippable protective layer and the surface protective layer; Performing hot bending forming on the substrate with the coating to obtain a formed body; The molded body is cleaned with a cleaning liquid to remove the coating, wherein the cleaning liquid includes an alkaline substance.
24. The hot bending forming method according to claim 23, characterized in that: The pH value of the cleaning solution is 11-13; and / or During the cleaning process, the temperature of the cleaning solution is 60°C-80°C.
25. The hot bending forming method according to claim 23, characterized in that: The cleaning solution also contains a surfactant; Optionally, the surfactant is selected from one or more of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, isomeric alcohol polyoxyethylene ether, secondary alcohol polyoxyethylene ether, and alkyl polyoxyethylene polyoxypropylene.
26. The hot bending forming method according to any one of claims 23 to 25, characterized in that: During the cleaning process, ultrasonic treatment is used as an aid; Optionally, the frequency of the ultrasonic treatment is 40kHz-80kHz, and the power is 10kW-20kW.
Citation Information
Patent Citations
Thermal insulation paint capable of being tempered, preparation method of thermal insulation paint and thermal insulation tempered glass prepared from thermal insulation paint
CN107189501A